Extra iron for baby pigs - B A Koch; G L Allee; D A Schoneweis; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
Ten mg. of iron per day fed orally 24 days in addition to 150 mg. injected when pigs were 3 days old did not significantly increase Hb of baby pigs. Neither did it increase average daily gain or weight-per-day-of-age at 32 days. We saw no symptoms of iron toxicity in treated pigs.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Iron; Hemoglobin; Toxicity